Abandono de tratamiento en pacientes pediátricos con diagnóstico de leucemia linfoblástica aguda - Francis Andrea Vásquez Triminio; Ligia Dolores Fú Carrasco; Rolando Aguilera Lagos (Revista Médica Hondureña)
Introduction: Withdrawal from antineoplastic treatment is the discontinuation of contact with healthcare person-nel for thirty days or more after initiation of therapy. Objective: To determine the proportion of treatment abandonment in paediatric patients diagnosed with acute lymphoblastic leukaemia. Methods:Retrospective descriptive study carried out in Outpatient Paediatric Haemato-Oncology, Hospital Escuela, period June 2010 to June 2020. We considered 690 paediatric patient records with a diagno-sis of acute lymphoblastic leukaemia; randomly selecting a sample of 124 records. Using the statistical programme Epi Info 7, 95% confidence level, prevalence 23%, type II error 6.7%. No files were excluded. For the analysis, descriptive statistics, Fisher’s exact test and calculation of the proportion of treatment abandonment were used. The protocol was approved by the ethics committee. Results: Mean age 8.9 years (+/-9.0, range 1.5 to 18 years); sex male 50.8% (63/124). Treatment dropout was 4.0% (5/124; 95%CI: 1.32-9.16). The main causes of dropout were parental migration to another country 2.4% (3/124), mother’s illness 0.8% (1/124) and in one case the cause was unknown. Discussion: The proportion of treatment dropout in paediatric patients with acute lymphoblastic leukaemia was 4.0%, low compared to the literature, and the main cause of dropout was due to parental migration to another country 2.4% (3/124), mother’s illness 0.8% (1/124) and in one case the cause was unknown. Discussion: The dropout rate of paediatric patients with acute lymphoblastic leukaemia was 4.0%, low compared to the literature, with the main cause of dropout being parental migration to another country.